2016
DOI: 10.1007/s10620-016-4195-1
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Gastrointestinal Manifestations of Inflammatory Bowel Disease May Be Less Common Than Previously Reported

Abstract: . (2016) Extra-gastrointestinal manifestations of inflammatory bowel disease may be less common than previously reported. Digestive Diseases and Sciences, 61 (9).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…Our patient's history of seronegative arthritis may be associated with her skin disease. Affected patients exemplify a triad of IBD, PG, and seronegative arthritis concurrently [7]. PG has rarely been documented to occur with seronegative arthritis but without IBD -however, our patient is one such case [6].…”
Section: Discussionmentioning
confidence: 69%
“…Our patient's history of seronegative arthritis may be associated with her skin disease. Affected patients exemplify a triad of IBD, PG, and seronegative arthritis concurrently [7]. PG has rarely been documented to occur with seronegative arthritis but without IBD -however, our patient is one such case [6].…”
Section: Discussionmentioning
confidence: 69%
“…Some researchers have suggested that the systemic inflammatory response may modulate the host microbiome of IBD, and has received increased attention [23,24]. Lots of studies have indicated that effective and efficient therapy could significantly control clinical symptoms (extraintestinal manifestations), reduce relapse, maintain remission, and improve the quality of life [25][26][27]. Therefore, selecting an ideal non-invasive test is increasingly expected and needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of patients with this complication in our study made it impossible to conclude any relationship with the LY75 SNPs. As the prevalence of erythema nodosum as an extra-intestinal symptom of CD is 2.3% [32], larger studies are needed to conclude if LY75 SNPs are related to this complication in Japanese CD patients.…”
Section: Discussionmentioning
confidence: 99%